2011
DOI: 10.1007/s11764-011-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Work ability of survivors of breast, prostate, and testicular cancer in Nordic countries: a NOCWO study

Abstract: More attention should be paid to assisting cancer survivors in work life, particularly those who have chronic diseases or have undergone chemotherapy. Although most factors affecting the work ability of the survivors and reference subjects were the same, survivors' work ability seemed to be particularly sensitive to avoidance behavior. The results suggest that there is a need to improve communication at the workplace and develop supportive leadership practices in order to avoid isolating behavior towards cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 35 publications
(54 reference statements)
2
56
1
Order By: Relevance
“…In addition, many researchers have demonstrated that cognitive impairment affects perceived work ability in survivors (Calvio, Peugeot, Bruns, Todd, & Feuerstein, 2010;de Boer et al, 2008;Feuerstein, Hansen, Calvio, Johnson, & Ronquillo, 2007;Hansen, Feuerstein, Calvio, & Olsen, 2008;Pryce, 2007;Taskila, Martikainen, Hietanen, & Lindbohm, 2007;Von Ah, Habermann, et al, 2013). In a large cohort study of 1,490 employed survivors and 2,796 reference participants, survivors had significantly lower levels of perceived work ability than healthy controls (Lindbohm et al, 2012). Perceived work ability, or the capability to manage job demands (Ilmarinen & Tuomi, 2004), has been associated with job stress (Kinnunen, Parkatti, & Rasku, 1994), and several studies have confirmed that poor work ability predicts loss of work productivity, retirement intentions, long-term absence, early retirement, need for rehabilitation, and work disability (Alavinia, de Boer, van Duivenbooden, Frings-Dresen, & Burdorf, 2009;Kuoppala, Lamminpaa, Vaananen-Tomppo, & Hinkka, 2011;Salonen, Arola, Nygard, Huhtala, & Koivisto, 2003;Sell et al, 2009).…”
Section: Cancer-and Treatment-related Factorsmentioning
confidence: 97%
“…In addition, many researchers have demonstrated that cognitive impairment affects perceived work ability in survivors (Calvio, Peugeot, Bruns, Todd, & Feuerstein, 2010;de Boer et al, 2008;Feuerstein, Hansen, Calvio, Johnson, & Ronquillo, 2007;Hansen, Feuerstein, Calvio, & Olsen, 2008;Pryce, 2007;Taskila, Martikainen, Hietanen, & Lindbohm, 2007;Von Ah, Habermann, et al, 2013). In a large cohort study of 1,490 employed survivors and 2,796 reference participants, survivors had significantly lower levels of perceived work ability than healthy controls (Lindbohm et al, 2012). Perceived work ability, or the capability to manage job demands (Ilmarinen & Tuomi, 2004), has been associated with job stress (Kinnunen, Parkatti, & Rasku, 1994), and several studies have confirmed that poor work ability predicts loss of work productivity, retirement intentions, long-term absence, early retirement, need for rehabilitation, and work disability (Alavinia, de Boer, van Duivenbooden, Frings-Dresen, & Burdorf, 2009;Kuoppala, Lamminpaa, Vaananen-Tomppo, & Hinkka, 2011;Salonen, Arola, Nygard, Huhtala, & Koivisto, 2003;Sell et al, 2009).…”
Section: Cancer-and Treatment-related Factorsmentioning
confidence: 97%
“…), and low workplace support and organisational commitment (Lindbohm et al . ). It is also recognised that people treated for cancer report a variety of problems relating to their return to work including job loss, demotion, unwanted changes in tasks, problems with employers and co‐workers, personal changes in attitudes to work and diminished physical capacity (Maunsell et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of studies concerning cancer survivors' return to work, researchers use quantitative methodo-logies, none of which address specific issues relating to HCPs (Bradley et al 2002;Steiner et al 2004;Farley Short et al 2005Pryce et al 2007;Tamminga et al 2010;Groeneveld et al 2012;Lindbohm et al 2012). There is a clutch of UK studies using qualitative methodologies predominantly with samples of breast cancer survivors (Main et al 2005;Kennedy et al 2007;Johnsson et al 2010) and an American qualitative study published in two parts Picard et al 2004) that report nurses' experiences as cancer survivors.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Other qualitative studies demonstrated the importance of workplace support and improved communication [36,37] for successful RTW [14,15,20,38]. Also, social support from health services and workplace adaptations seemed to affect patients' RTW experiences [39].…”
Section: Workplace Support: Genuine Recognition Of the Vulnerabilitymentioning
confidence: 99%